Prevalence of Latent Tuberculosis (LTB) Among Pregnant Women in a High Burden Setting in Sudan using Interferon Gamma (IFN- γ) Releasing Assay (IGRA) - Yassin, Khalid; Ahmed, Elbashir G.E.; Musa, Abdualmoniem O.; Hamdan, Hamdan Z.; Abuzied, Nadir; Fagear, Asma A.; Adam, Gamal K.; Abdalla, Tajeldin M.; Ali, AbdelAziem A. (Current Women's Health Reviews, 2019)
Background: Accurate timing for diagnosis and treatment of latent tuberculosis (LTB) is important to reduce morbidity and mortality for both mother and child. Objectives: To investigate the prevalence rate of LTB and its associated factors during pregnancy using gamma interferon (IFN- γ) release assay (IGRA). Methods: A cross-sectional facility-based study carried out in Kassala hospital, Eastern Sudan between January and March 2015. Results: Two hundred and forty-nine women were enrolled in this study and 18.1% (45/249) had confirmed positive for M. tuberculosis infection using IGRA. The mean age, parity and gestational age of the LTB patients were 29.6 (4.4), 2.2 (1.2) and 21.9 (8.8), respectively. The vast majority of these patients was of rural residence (72.7%), housewives (91.1%) and illiterate (73.3%). More than half (25, 55.6%) gave a history of contact with tuberculosis patients, 26.7% (12/45) were vaccinated and 11.1% (5/45) had a medical history of diabetes mellitus. In logistic regression model, while age, parity, education, occupation, size of family members, smoking, BCG status and medical history of diabetes mellitus were not associated with latent tuberculosis during pregnancy, history of contact with TB patients (OR=13.5; CI=5.6 to 32.5; P<0.001) and rural residence (OR=0.3; CI=0.1 to 0.7; P=0.006) was significantly correlated to LTB in pregnancy. Conclusion: Thus, screening of all pregnant women living in high burden setting of tuberculosis is recommended even in the absence of overt clinical signs of the disease.
Keywords: diabetes mellitus